Environmental Assessment of Lead Contaminated Site from Artisanal Gold Mining in Bagega Community, Nigeria - , Alaba O. Clement; , Opafunso Z. Olaniyan (Archives of Current Research International, 2016)
Aims: The study assesses the extent of lead pollution in contaminated site from artisanal gold mining for remediation purposes. Study Design: Experimental design was used in field sampling of soil and water samples based on the land use and sources of water. Study Area and Methodology: Bagega Community is located in Anka Local Government Areas in Zamfara State between the longitude 5.999E and 6.049E; And latitude 11.873N and 11.861N. Stratified random sampling method was used to collect soil samples from sites SSA, SSB, SSC, SSD and SSE while water samples were collected from wells, boreholes and ponds in accordance with ASTM D 6970 and EPA standard procedures. The lead values in soil and water samples were determined in accordance with ASTM D 3559 and ASTM D 1976 standard methods. The data were analyzed using inferential statistical methods of multivariable mean with use of the turkey test to separate the mean, while the significance of lead pollution was determined with one sample t – test. Results: The mean value of lead in SSA was 3521.31 mg/kg, SSB was 3628.76 mg/kg, SSC was 3546.19 mg/kg, SSD was 9012.44 mg/kg and SSE was 7251.72 mg/kg, while the one sample t – test established that the mean value of lead in soil sample was significantly different from 400 mg/kg USEPA standard. The lead value in well and borehole water were within the WHO standard except the unprotected wells and boreholes with lead values as high as 131.0 µg/l and 30.33 µg/l in unprotected wells and boreholes. Meanwhile, 67.0% of the pond water recorded lead values that exceeded the WHO standard with a mean value of 1103.33 µg/l. Conclusion: The soil and water samples with lead values that were above USEPA and WHO standards should be subjected to remediation.